Design of Skill Enhancement Module for Pharmacy Students - Need of the Hour - Lysetty, Shanthi; Kannan, Siva Kumar; Naha, Anup; Nayak, Usha Yogendra; Ligade, Virendra (Indian Journal of Pharmaceutical Education and Research, 2022)
Skill industries, such as manufacturing and services, are growing at a rapid rate. It is estimated that there is a huge demand for skilled employees in the future. But India’s skilled workforce is very low. The country is currently facing a dual dilemma of the extreme shortage of highly-trained, high-quality work yet as non-employment of large parts of educated people with very few or no job skills. The issue of skill development in India is so relevant to demand and supply levels. The pharmaceutical sector is developing at a rapid pace, but challenges faced by the pharmaceutical industries are outdated skilled workforce. This is due to the outdated curriculum followed in the majority of universities and lack of industrial exposure, limited industry interfaces, lack of appropriate skills and education. Thus there is a need to develop a skill development module and incorporate it as a training program. Total quality management and innovation ecosystem to be introduced in pharmacy to improve the current situation. This article emphasizes on skill gap requirements, developing skill modules for pharmacy students, design of a curriculum, introduction of practice school, various strategies and pedagogical techniques to be introduced to develop the skills of the students and make them ready for specialised job roles.
Keywords: Skill; Curriculum; Design; Learning; Pharmacy education